The protein C pathway : linking inflammation and coagulation - White, Desmond Barry (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2000)
Activated protein C (APC) is a natural anticoagulant and plays a pivotal role in coagulation homeostasis by inhibiting factors Villa and Va. Recent data suggests that APC also negatively regulates pro-inflammatory cytokine production and is protective in animal models of sepsis. The dual functional properties of the protein C (PC) pathway are particularly relevant to severe meningococcaemia which is associated with severe acquired protein C (APCD) deficiency and a high risk of morbidity and mortality. The mortality is primarily caused by cytokine driven multiorgan failure while the major morbidity results from the development of extensive micro vascular thromboses (purpura fulminans). Severe APCD is likely to be an integral component in the development of purpura fulminans, however, it may also lead to the loss of an important negative regulator of host inflammatory response and thereby contribute to the mortality associated with cytokine mediated multiorgan failure.
Keywords: Medicine, M.D.; M.D. Trinity College Dublin